ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH RIGHT ISSUE (STUDI EMPIRIS PADA PERUSAHAN YANG TERDAFTARDI BURSA EFEK INDONESIA TAHUN 2017-2020) - Al Qoidah, Istiqomah; Moh Halim; Rendy Mirwan Aspirandi (Juremi: Jurnal Riset Ekonomi, 2021)
ABSTRACT The Purpose of this study was to analyze the diffrences in financial performance before and after right issue.. The variables used are return on assets (ROA), debt to equity ratio (DER), current ratio (CR) and price to book value (PBV). The data taken is 2 years before the rights issue, namely in 2017-2018 and after the rights issue 2019-2020. The sample used as many as 20 companies listed on the IDX. The results of the study show that there is no effect on return on assets between before and after the rights issue to earn profits not only through the rights issue. The debt to equity ratio has an effect between the time before and after the rights issue. This shows that the company uses the proceeds from the rights issue. to pay off his debts. The current ratio has no effect between the time before and after the right issue. This shows that the company in paying off its short-term obligations with its assets, there is no comparison between the time before and after the right issue. Price to book value has no effect between the time before and after the right issue. . This shows that the company after carrying out the rights issue activity that most of the proceeds from the rights issue were used for industrial capital accumulation.